(untitled) (Al-Farooq Journal of Sciences, 2026)
This research had one main objective which is to find out whether studying online is a good choice or not. An increasing number of students are now choosing online courses. They find it more flexible, practical and saves a lot of time. This shift in pedagogical standard is forcing academic organizations to reevaluate their ways of delivering their course content. The researcher wanted to find if there are any problems that face those students while learning online. Data were collected in qualitative ways. Thus, the researcher conducted interviews with 10 university students who are studying English. Results showed that most of the students prefer studying online as it saves time, effort and no need to go anywhere to study. Yet many others faced a lot of obstacles such as weak connection, financial issues and disturbing notifications of other application on line. Moreover, the result of this research will help the students to progress their ways of learning English online. Also the results may encourage the teachers to discover more techniques and methods on teaching English online.